Etika Pemasaran Islam dan Loyalitas Merek Perbankan Syariah: Peran Mediasi Kepercayaan dalam Tinjauan Literatur Terfokus 2015–2025 - Yudhi Novriansyah; Herawati; Muhammad Asman (LPPM STEI Kanjeng Sepuh Gresik Jawa Timur, 2026)
Islamic banking is growing rapidly, yet how Islamic marketing ethics builds trust and brand loyalty remains fragmented. This study maps relationships among Islamic marketing ethics, trust, and brand loyalty in Islamic banking (2015–2025) via a focused/purposive literature review. A search across five databases (Scopus, Web of Science, Google Scholar, DOAJ, Sinta; last search 20 June 2026) yielded eight purposively selected studies, chosen for methodological quality, citation count, and method/region representativeness, then assessed by two independent reviewers using CASP checklists (Cohen’s kappa = 0.85; 95% CI: 0.69–0.93; “almost perfect”). A narrative synthesis was conducted. Results show three of four studies report a positive link between Islamic marketing ethics and trust; of six studies on the trust/brand image–loyalty path, four report a direct relationship, two partial mediation. The novelty is a serial mediation model integrating ethics, trust, Islamic brand image, and loyalty, moderated by religiosity and Islamic financial literacy, with a conceptual extension toward digital trust and marketing ethics. Theoretically, this offers a framework extensible to digital contexts; practically, it underscores ethics as core to Islamic bank marketing and financial inclusion. Limitations include the purposive scope, dominance of English-language sources, and predominantly cross-sectional evidence limiting claims to association rather than causation.